Advances and challenges of sodium ion batteries as post lithium ion batteries. Issue 65 (16th July 2015) - Sawicki, Monica; Shaw, Leon L.
<x xml:space="preserve">Abstract</x> Na3MnCO3PO4 offers a specific capacity of 176.7 mA h g−1, reaching 92.5% of its theoretical if electronic conductivity is sufficient.106